2011
DOI: 10.1016/j.molcata.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-catalysed hydrogenation of esters using tripodal phosphine ligands

Abstract: 24/09/12 meb. Author version attached, OK to publish

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…Undoubtedly, the precious metal-based catalysts are still remain the leading catalysts for hydrogenation such as palladium [25][26][27], platinum [28][29][30], rhodium [31,32], ruthenium [33,34] and aurum-based [35][36][37] systems, even though their widespread applications are limited by their low earth-abundance and high cost. In order to solve these problems, various non-precious metal catalysts [38][39][40], especially nickel-based catalysts [3,[39][40][41] have been developed as economical alternatives in hydrogenation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, the precious metal-based catalysts are still remain the leading catalysts for hydrogenation such as palladium [25][26][27], platinum [28][29][30], rhodium [31,32], ruthenium [33,34] and aurum-based [35][36][37] systems, even though their widespread applications are limited by their low earth-abundance and high cost. In order to solve these problems, various non-precious metal catalysts [38][39][40], especially nickel-based catalysts [3,[39][40][41] have been developed as economical alternatives in hydrogenation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently derivatives with less sterically demanding phosphines, or more forcing conditions were implemented to enforce a κ 3 -coordination mode. NP 3 R derivatives bearing ethyl (N(CH 2 PEt 2 ) 3 , NP 3 Et , 132) [53], isopropyl (N(CH 2 P i Pr 2 ) 3 , NP 3 iPr , 133) [54] and cyclopentyl (N(CH 2 PCyp 2 ) 3 , NP 3…”
Section: Nitrogen (N(ch 2 Pr 2 ) 3 )mentioning
confidence: 99%
“…The diphenyl-(NP 3 Ph , 113) and diethyl-phosphino nitrogen-centered ligands (NP 3 Et , 132) were evaluated for their ability to hydrogenate the industrially relevant ester dimethyl oxalate (DMO) to ethane-1,2-diol (ED) via methyl glycolate (MG) (Scheme 31), but it was found that both of these ligands underperformed when compared to Ph [53]. The catalysts were formed in situ from [Ru(acac) 3 ] (acac = acetylacetone) and triphosphine, and N-centered ligands all displayed longer induction periods, where hydrogen was being consumed but no DMO conversion was observed by analysis of sampled aliquots and headspace gas.…”
Section: Nitrogenmentioning
confidence: 99%
See 2 more Smart Citations